2011
DOI: 10.1186/1471-230x-11-107
|View full text |Cite
|
Sign up to set email alerts
|

The transhepatic endotoxin gradient is present despite liver cirrhosis and is attenuated after transjugular portosystemic shunt (TIPS).

Abstract: BackgroundTranslocation of gut-derived bacterial products such as endotoxin is a major problem in liver cirrhosis.MethodsTo assess the hepatic clearance of bacterial products in individuals with cirrhosis, we tested concentrations of Gram-negative bacterial lipopolysaccharide (LPS), LPS-binding protein (LBP), and the precursor of nitric oxide (NO), L-arginine, in a cohort of 8 stable patients with liver cirrhosis before and after elective transjugular portosystemic shunt (TIPS) implantation, including central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…As an additional survival strategy, S. typhi has evolved mechanisms to downregulate the inflammatory response it may induce in its host 40. There is nothing intrinsically poisonous about this endotoxin; what is important is the host response to it 41,42…”
Section: Microbial Factorsmentioning
confidence: 99%
“…As an additional survival strategy, S. typhi has evolved mechanisms to downregulate the inflammatory response it may induce in its host 40. There is nothing intrinsically poisonous about this endotoxin; what is important is the host response to it 41,42…”
Section: Microbial Factorsmentioning
confidence: 99%
“…Some studies have investigated blood samples taken during transjugular intrahepatic portosystemic shunt (TIPS) procedures, comparing blood samples from the hepatic vein and the portal vein. In one study it was found that cirrhotic livers retain the capacity for clearance of bacterial endotoxin from the portal venous blood and that TIPS implantation attenuates this clearance [40]. In this study, LPS-binding protein was measured by limulus amebocyte lysate assay [41].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…However, a recent study showed that TIPS increased LPS levels in peripheral blood 1 h after stent placement in patients with acute, uncontrolled bleeding [ 10 ]. This phenomenon might result from short-term hemodynamic changes caused by procedural trauma or acute bleeding [ 11 ].…”
Section: Discussionmentioning
confidence: 99%